Optimizing Taman Pustaka 'Aisyiyah Dzakiya through Storytelling Training for 'Aisyiyah Bustanul Athfal Kindergarten Teachers in Minggir (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Taman Pustaka 'Aisyiyah Dzakiya is a reading park under the auspices of the Pimpinan Cabang 'Aisyiyah Minggir Cultural Institute which is located in the Al-Umar Parakan Wetan Sendangsari Minggir Mosque complex, Sleman Yogyakarta. Taman Pustaka 'Aisyiyah Dzakiya was founded in 2019 after receiving the first grant from the National Library of Indonesia. The main problems faced include that Taman Pustaka 'Aisyiyah Dzakiya has not upgraded its reading books or other supporting facilities, so its resources are still limited. The management carried out by volunteers is considered less than optimal, because there is no strong motivation from the management to maximize the value of this reading park. To be able to overcome this problem, the service team tried to provide a solution by creating a program whose aim was to increase the value of the Taman Pustaka 'Aisyiyah Dzakiya using a learning method approach through stories. So, the activity that will be carried out is storytelling training for kindergarten and PAUD teachers in Kapanewon Minggir. Apart from that, another activity that the proposing team offers as a solution to improve the functionality of Taman Pustaka 'Aisyiyah Dzakiya is improving the physical facilities of the library, namely by repairing damaged cupboards and increasing the collection of reading books in the library. Methods for implementing activities include preparation and coordination, repair and upgrading of facilities, implementation of storytelling training, and evaluation and monitoring.